Brief and Indirect Exposure to Natural Environment Restores the Directed Attention for the Task - Kimura, Tsukasa; Yamada, Tatsuya; Hirokawa, Yohko; Shinohara, Kazumitsu (Frontiers in Psychology, 2021)
The mental fatigue elicited by working and studying is consumed mental resources, thereby it is elicited a decline performance and an increase mental stress. Long-term continuous work and study, which is typical for modern workers and students, can increase mental fatigue and health risks. Previous studies reported that the natural environment (i.e., forest and waterside) has a restorative of mental resources (i.e., attention) and reducing stress. However, it is difficult for urban workers and students to take sufficient breaks in real natural environment. We conducted an experiment to examine whether brief and indirect exposure to the natural environment elicits a restorative of attention and reducing stress. Twenty-five undergraduate and graduate students belonged in the university of modern city participated in the experiment. The experiment involved measuring the changes in participants’ task performance (i.e., sustained attention to response task; SART) and subjective mental workload (i.e., arousal, valence, and NASA-TLX) while an attention restoration was indexed from physiological response (i.e., skin conductance level: SCL) over time. The participants had two types of resting periods in the middle of the task, i.e., by looking at a blank display (simple break) or watching a nature video including scenes of, e.g., a forest, small waterfall, and rustling leaves (nature break). The results indicate that the natural environment indirectly depicted through the nature videos did not affect task performance and subjective mental workload but decreased the SCL. The results of physiological response suggest that having rest periods depicting the natural environment, even if indirectly and briefly, can restore the directed attention (i.e., mental resources) for the task. This experiment revealed a useful method of resting for urban workers and students to restore their attention to a task.